Toleransi Antar Aliran Beragama Agama Islam dalam Perspektif Muhammadiyah - Miswala, Sakana Tiswi; Maksum, Muh. Nur Rochim (INC- Islam Nusantara Center, 2024)
This research examines tolerance between sects in Islam from the perspective of Muhammadiyah. Different perspectives in Islam have given rise to various sects that often intersect with each other. The purpose of this research is to find out the limits of tolerance between Muslims of different sects and Muhammadiyah's attitude towards certain sects such as LDII, Ahmadiyah, Shia, and Kejawen. This research was conducted because of the importance of understanding the attitude of tolerance in Islamic diversity to maintain community harmony. The method used is qualitative research based on literature study. The results show that Muhammadiyah puts forward the principles of moderation and openness in addressing differences in sects, but still has boundaries based on Islamic teachings that are firmly held. The findings are expected to provide a better understanding of tolerance in Islamic diversity. Penelitian ini mengkaji toleransi antar sekte dalam Islam dari perspektif Muhammadiyah. Perbedaan cara pandang dalam Islam telah memunculkan berbagai aliran yang seringkali bersinggungan satu sama lain. Tujuan dari penelitian ini adalah untuk mengetahui batas-batas toleransi antar umat Islam yang berbeda aliran dan sikap Muhammadiyah terhadap aliran-aliran tertentu seperti LDII, Ahmadiyah, Syiah, dan Kejawen. Penelitian ini dilakukan karena pentingnya memahami sikap toleransi dalam keberagaman Islam untuk menjaga kerukunan umat. Metode yang digunakan adalah penelitian kualitatif berdasarkan studi literatur. Hasil penelitian menunjukkan bahwa Muhammadiyah mengedepankan prinsip-prinsip moderasi dan keterbukaan dalam mwords: tolerance between sects, Muhammadiyah perspective, Islamic tolerance.enyikapi perbedaan aliran, namun tetap memiliki batasan-batasan berdasarkan ajaran Islam yang dipegang teguh. Temuan ini diharapkan dapat memberikan pemahaman yang lebih baik tentang toleransi dalam keberagaman Islam.